Synthesis and LPG sensing properties of nano-sized cadmium oxide - Waghulade, R. B.; Patil, P. P.; Pasricha, Renu (Talanta, 2007)
This paper reports the synthesis and liquid petroleum gas (LPG) sensing properties of nano-sized cadmium oxide (CdO). The nano-sized CdO powder was successfully synthesized by using a chemical co-precipitation method using cadmium acetate and the ammonium hydroxide, as starting materials and water as a carrier. The resulting nano-sized powder was characterized by X-ray diffraction (XRD) measurements and the transmission electron microscopy (TEM). The LPG sensing properties of the synthesized nano-sized CdO were investigated at different operating temperatures and LPG concentrations. It was found that the calcination temperature and the operating temperature significantly affect the sensitivity of the nano-sized CdO powder to the LPG. The sensitivity is found to be maximum when the calcination temperature was 400 degrees C. The sensitivity to 75 ppm of LPG is maximum at an operating temperature 450 degrees C and it was found to be similar to 34 1 %. The response and recovery times were found to be nearly 3-5s and 8-10s, respectively. The synthesized nano-sized CdO powder is able to detect up to 25 ppm for LPG with reasonable sensitivity at an operating temperature 450 degrees C and it can be reliably used to monitor the concentration of LPG over the range (25-75 ppm). The experimental results of the LPG sensing studies reveal that the nano-sized CdO powder synthesized by a simple co-precipitation method is a suitable material for the fabrication of the LPG sensor. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: chemical co-precipitation; Gas sensor; LPG; nano-sized CdO